An IR navigation system for pleural PDT - Zhu, Timothy C.; Liang, Xing; Kim, Michele M.; Finlay, Jarod C.; Dimofte, Andreea; Rodriguez, Carmen; Simone, Charles B.; Friedberg, Joseph S.; Cengel, Keith A. (Frontiers in Physics, 2015)
Pleural photodynamic therapy (PDT) has been used as an adjuvant treatment with lung-sparing surgical treatment for malignant pleural mesothelioma (MPM). In the current pleural PDT protocol, a moving fiber-based point source is used to deliver the light. The light fluences at multiple locations are monitored by several isotropic detectors placed in the pleural cavity. To improve the delivery of light fluence uniformity, an infrared (IR) navigation system is used to track the motion of the light source in real-time at a rate of 20 - 60 Hz. A treatment planning system uses the laser source positions obtained from the IR camera to calculate light fluence distribution to monitor the light dose uniformity on the surface of the pleural cavity. A novel reconstruction algorithm is used to determine the pleural cavity surface contour. A dual-correction method is used to match the calculated fluences at detector locations to the detector readings. Preliminary data from a phantom shows superior light uniformity using this method. Light fluence uniformity from patient treatments is also shown with and without the correction method.